PENDIDIKAN ISLAM DI MALAYSIA: JENIS, JENJANG, KEBIJAKAN, DAN TUJUAN PENDIDIKAN - Aslindah, Andi (UIN Alauddin Makassar, 2015)
Abstract: TheÂ purpose of education in Islam is among others to form Muslim personal in the development of spiritual, physical, emotional intellectual and social. It is not only produced good citizens but also covers the formation of a complete human capital in terms of religious and worldly life. In addition, the education that is based on the teachings of Islam also aimed at producing righteous human that can meet the needs of the world and life in the hereafter. The main focus of this article is about theÂ development of Islamic Education in Malaysia, the type and level of education, and education policy in Malaysia.Abstrak: Tujuan Pendidikan Islam adalah membentuk pribadi muslim yang mengembangkan potensi spiritual, fisik, emosi, intelektual dan sosial. Tujuan pendidikan islam bukan hanya menghasilkan orang yang baik tapi juga mencakup pembentukan manusia yang bersifat religious dan duniawi. Lebih banjut pendidikan harus didasarkan pada pengajaran Islam yang bertujuan menghasilkan manusia yang berkualitas yang dapat memenuhi kebutuhan dunia dan kehidupan di akhirat. Fokus utama dari penelitian ini adalah pengembangan pendidikan Islam di Malaysia, jenis dan tingkatan pendidikan di Malaysia, dan kebijakan pendidikan di Malaysia.